The Analysis of Nuclear Materials and Their Environments - Degueldre, Claude André (Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of passive and interactive analytical techniques for nuclear materials. The book aims to update readers on new techniques available and provide an introduction for those who are new to the topic or are looking to move into actinides and nuclear materials science. The characterization of actinide species and radioactive materials is vital for understanding how these elements and radioactive isotopes are formed and behave and how these materials can be improved. The analysis of the actinides or radioactive materials goes beyond spent fuel science to the applicable complete fuel cycle and including analysis of reactor materials. Provides an overview of the methodology and of the systematisation of passive and interactive analytical techniques for nuclear material analysis; Covers the main areas of radioactive materials characterization including sampling and sample preparation and sub-sample treatment or separation; Includes analysis of the complete fuel cycle of radioactive materials.
Keywords: Materials science.; Nuclear energy.; Nuclear chemistry.; Quality control.; Reliability.; Industrial safety.; elektronické knihy; electronic books